2013
DOI: 10.7314/apjcp.2013.14.11.6519
|View full text |Cite
|
Sign up to set email alerts
|

TP63 Gene Polymorphisms, Cooking Oil Fume Exposure and Risk of Lung Adenocarcinoma in Chinese Non-smoking Females

Abstract: -1.01, P=0.059). Our results showed that exposure to cooking oil fumes was associated with increased risk of lung adenocarcinoma in Chinese nonsmoking females (adjusted OR=1.58, 95%CI=1.11-2.25, P=0.011). However, we did not observe a significant interaction of cooking oil fumes and TP63 polymorphisms. Conclusion: TP63 polymorphism might be a genetic susceptibility factor for lung adenocarcinoma in Chinese non-smoking females, but no significant interaction was found with cooking oil fume exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…In our previous published papers, cooking oil fume exposure was found to be significantly associated with the risk of lung cancer in non-smoking females [1418], so in the present study we analyze the interaction between SNPs and cooking oil fume exposure. For cooking oil fume exposure, participants were asked about the frequency of cooking and types of oils.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous published papers, cooking oil fume exposure was found to be significantly associated with the risk of lung cancer in non-smoking females [1418], so in the present study we analyze the interaction between SNPs and cooking oil fume exposure. For cooking oil fume exposure, participants were asked about the frequency of cooking and types of oils.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous reports showed that household exposure to cooking oil fume was associated with the risk of non-smoking female lung cancer [1418]. A study in a high incidence population in North East India found that the interaction of XRCC1Gln/Gln genotype with exposure of exposure of cooking oil fumes was significantly associated with increased risk for lung cancer [19].…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to welding fumes at work place (Mannetje et al, 2012), cooking fumes (Yin et al, 2013), sedentary living (Yang et al, 2003), family history (Cote et al, 2012), exposure to wood dust (Bhatti et al, 2011), alcoholism (Bagnardi et al, 2010) and asbestos exposure (Markowitz et al, 2013) has also been reported in Caucasian, American, African and Asian populations as positive risk factors of lung cancer. But high OR value of 2.5 in Pakistani population for welding fumes in present study is higher than any other parts of the world.…”
Section: Causative Factorsmentioning
confidence: 99%
“…Exposure to cooking oil fumes might increase the risk of lung adenocarcinoma in Chinese nonsmoking females (adjusted OR=1.58, 95%CI=1.11-2.25, P=0.011). However, significant interaction of cooking oil fumes and TP63 polymorphisms was not observed [43]. Cao et al [44] demonstrated decreased cell viability, increased malondialdehyde (MDA) level, decreased superoxide dismutase (SOD) and glutathione (GSH) activities in a doseand time-dependent manner of CFs, which proved CFs may lead to toxicity in AEC II cells at a very low dose.…”
Section: B Cooking Fumes Effects On the Cellmentioning
confidence: 99%